Breast cancer histological classification: agreement between the Office for National Statistics and the National Health Service Breast Screening Programme - Gathani, T; Bull, D; Green, J; Reeves, G; Beral, V; Gathani, T; Bull, D; Green, J; Reeves, G; Beral, V (BioMed Central, 2005)
INTRODUCTION: Epidemiological studies rely on data supplied by central cancer registration sources to be timely, accurate and complete. Validation studies of such data at a national level are limited. Data collected for the Million Women Study was used to compare the level of agreement between the Office for National Statistics (ONS) and the National Health Service Breast Screening Programme (NHSBSP) in the recording of incident screen-detected breast cancer histology between 1996 and 2001. METHODS: 1.3 million women aged 50 to 64 years were recruited into the Million Women Study cohort via the NHSBSP. Incident screen-detected breast cancer histologies were notified separately by the ONS and NHSBSP. ICD-10 and ICD-02 ONS codes and NHSBSP histology data were similarly coded to allow for comparison in terms of cancer invasiveness and morphology. The statistical outcome measures are percentage agreement and the kappa statistic. RESULTS: A total of 5,886 incident screen-detected breast cancers were available for analysis. Of the 5,886 screen-detected cancers reported by the ONS and NHSBSP, 5,684 (96.6%, kappa = 0.9) agreed in terms of the degree of invasiveness. Of the 5,458 cancers that had been assigned a specific morphology code, there was exact agreement between the ONS and the NHSBSP in 4,922 cases (90.2%, kappa = 0.8). CONCLUSION: There is an excellent level of agreement between the ONS and NHSBSP in the recording of the histology of screen-detected breast cancer. From these results it is not possible to comment on which source of data is the more or less accurate, although the differences are very small.